Profile of HIV positive women attending a university clinic in Brazil - Silveira, Mariângela F; Santos, Iná S (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: HIV contamination among women has been increasing. In Brazil, over 250.000 HIV infections were registered between 1980 and 2002, of which 28% were among women. Knowing the characteristics of HIV+ women can contribute to their identification and for designing effective preventive programs. Objective: to identify socioeconomic, demographic, reproductive, lifestyle and behavioral characteristics of HIV+ women attending a specialized clinic in a middle sized Brazilian city. Methods: a standardized questionnaire was used for interviewing HIV+ women aged 15 years or more, addressing sexual behaviors, condom use and other individual characteristics. Results: of 340 women interviewed, 37.6% know about their HIV status for 3 years of more, and 52% were asymptomatic. Their mean age was 32.5 years; 68% were white; 38% had up to 4 years of schooling; and 88% had a family income below one minimum wage. Half of them were smokers. Regarding HIV prevention, 32% cited a good diet and 18% avoiding public toilets as recommended methods; 39% did not use a condom in their last intercourse, and 24% believed that HIV+ persons should not disclose their condition to any other person. Conclusion: the women studied are younger than the the national average for HIV+ women. Low schooling and income are risk factors that may affect the success of treatment schemes. They had undergone more frequent cervical cancer smears, suggesting greater concern among their doctors given their higher risk of cervical cancer. Many HIV+ women engage in unsafe sex, which is an important obstacle to the effective control of this epidemic.